2006
DOI: 10.1021/ja056086j
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Approach to the Synthesis of Sulfate Esters

Abstract: A comprehensive approach to the synthesis of sulfate esters was developed. This approach permits the direct and high-yielding synthesis of protected sulfate monoesters. Subsequent deblocking to reveal sulfate monoesters is accomplished in near-quantitative yield. The exceptionally stable neopentyl protecting group and the labile isobutyl protecting group were utilized in the synthesis of aromatic and aliphatic sulfate monoesters. Strategies for tuning protecting group reactivity were also explored and develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
118
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(119 citation statements)
references
References 21 publications
1
118
0
Order By: Relevance
“…To determine IC 50 values for C4-derived peptides, all proteins and peptides were tested at a final molar ratio of 1 3 ], which was prepared and introduced to the growing peptide chain using the method described previously (25,26 2 ) C4 peptides were synthesized by GL Biochem using Fmoc-strategy solidphase peptide synthesis. The modified and unmodified peptides were used at final concentrations of 5-500 mM.…”
Section: Measurement Of the Cleavage Of C4 By Protease Variantsmentioning
confidence: 99%
“…To determine IC 50 values for C4-derived peptides, all proteins and peptides were tested at a final molar ratio of 1 3 ], which was prepared and introduced to the growing peptide chain using the method described previously (25,26 2 ) C4 peptides were synthesized by GL Biochem using Fmoc-strategy solidphase peptide synthesis. The modified and unmodified peptides were used at final concentrations of 5-500 mM.…”
Section: Measurement Of the Cleavage Of C4 By Protease Variantsmentioning
confidence: 99%
“…An alternative strategy based on the use of the protected sulfonation reagent 8 [25,26] was investigated [27,28]. Following the procedure of Taylor [29], treatment of phenol 7 (0.3 M concentration in the reaction medium) with an excess of 8 in the presence of triethylamine and DMAP afforded the sulfate diester 10 in 94% yield.…”
Section: Synthesis Of Sulfated Metanephrinesmentioning
confidence: 99%
“…66,70 To overcome some of these problems, which also complicate the synthesis of other biologically relevant sulfate esters such as sulfated oligosaccharides and steroids, Simpson and Widlanski recently developed a general strategy for the synthesis of sulfate monoesters using alkyl protecting groups. 81 The authors found that neopentyl protected sulfate monoesters are exceptionally stable under strongly acidic and basic conditions, and they demonstrated that the neopentyl group can be quantitatively removed with sodium azide in dimethylformamide (DMF). They also described the preparation of Fmoc and Boc derivatives of neopentyl-protected sulfoTyr, emphasizing the potential usefulness of this strategy for solid-phase synthesis of sulfoTyr peptides.…”
Section: 74mentioning
confidence: 99%